Utilization of zakāt through entrepreneurship programs - Diyah Ariyani; Dini Rahmayanti (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
This study aims to analyze matters related to the distribution of zakat funds at the Semarang branch of Rumah Zakat through entrepreneurship programs and also things that are obstacles and drivers in the distribution of zakat. The method used in this study used qualitative research. The results of this study show that the distribution of zakat funds at Rumah Zakat Semarang is carried out productively and consumptively. And for the distribution of zakat funds at Rumah Zakat Semarang through an entrepreneurship program, it is carried out through the Senyum Mandiri program, which is community empowerment oriented towards integrated community empowerment. This empowerment is carried out in the ICD (Integrated Community Development) area as well as the scope of the village area. There are several empowerment programs, including Entrepreneurial assistance, Independent Development Center, and Productive Skills Training.